Three-dimensional high-thermal-conductivity asphalt-based carbon fiber composite material and preparation method thereof
By reserve Pin holes in the asphalt-based carbon fiber prepreg and erecting Z-pin with a magnetic field, combined with film covering of high thermal conductivity of high thermal conductivity, the problem of low Z-directional thermal conductivity in the prior art is solved, and a stable balance between Z-directional thermal conductivity and in-plane thermal conductivity is achieved, which is suitable for heat management of electronic products.
Patent Information
- Application Number
- CN202510885094.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-30
- Publication Date
- 2025-07-29
- Estimated Expiration
- 2045-06-30
AI Technical Summary
The Z-direction thermal conductivity of the existing asphalt-based carbon fiber composite materials is extremely low, blocking the heat transfer path from the internal device to the outer surface of the shell. The existing methods destroy the in-plane thermal conductivity while increasing the Z-direction thermal conductivity or cause instability of the thermal conductivity.
By reserve Pin holes in the asphalt-based carbon fiber prepreg and using a magnetic field to erect the asphalt-based carbon fiber chopped Z-pin in a state consistent with the Z direction, combined with a film of high thermal conductivity material to build a stable Z-conductive thermal path.
It achieves efficient and stable Z-direction thermal conductivity improvement, ensuring that the in-plane thermal conductivity is not affected, and diffuses heat through secondary heat dissipation, which is suitable for heat management of electronic products.
Smart Images

Figure CN120382670A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the fields of carbon fiber composites and thermal conductive materials, and particularly to a three-dimensional highly thermal conductive pitch-based carbon fiber composite and a preparation method thereof. Background Art
[0002] The in-plane thermal conductivity of existing pitch-based carbon fiber composites is relatively high, which can reach 300 - 400 W / m•K. However, since the carbon fiber layers are connected by a resin matrix, and the thermal conductivity of the resin is extremely low, the heat transfer path in the Z direction is blocked, resulting in an extremely low thermal conductivity in the Z direction of the material. At best, it only achieves about 0.8 W / m•K. The improvement of the thermal conductivity in the Z direction is extremely important for electronic devices to transfer the heat of internal components to the outer surface of the housing.
[0003] The following are several existing technologies for improving the Z-direction thermal conductivity of carbon fiber composites.
[0004] (1) Combine the pitch-based carbon fiber resin matrix with carbon nanotubes to improve the Z-direction thermal conductivity of the material by utilizing the characteristics of carbon nanotubes. For example, CN111319279A is a modified pitch-based carbon fiber composite for spacecraft payload structures, but the technical drawback is that it destroys the fiber continuity in the plane, thereby reducing the in-plane thermal conductivity. Another example is CN117326882A, a method for improving the Z-direction thermal conductivity of pitch-based carbon fiber composites, but the technical drawback is that due to the easy breakage of carbon fiber filaments, the Z-direction heat transfer path is unstable, resulting in the maximum Z-direction thermal conductivity shown in the examples of this patent being only 3 W / m•K.
[0005] (2) Improve the mechanism in the preparation of pitch fiber filaments to enhance the Z-direction thermal conductivity of the material. For example, CN111962294A, a high thermal conductivity composite and its preparation method proposed by Hunan Dongying. However, the technical drawback is that the Z-direction heat transfer path is unstable, and there are differences in the Z-direction thermal conductivity parameters of the material.
[0006] (3) Implant Pins in the Z direction of the material to establish a heat transfer channel. For example, CN109049865A, a three-dimensional heat transfer channel composite and its preparation method. However, the technical drawback is that the Z-pins are broken or damaged due to the resistance of the carbon fiber layers during implantation, and the Z-direction heat transfer path is unstable. The maximum Z-direction thermal conductivity shown in the examples of this patent only reaches 10 W / m•K. And after the heat is conducted from one side of the material to the other side in the Z direction, it converges into a point, resulting in extremely concentrated heat. Another example is CN109265919A, a 3D thermal conductive composite and its preparation method. The technical drawback of this method is that the efficiency is low and the accuracy cannot be guaranteed during the manual insertion of Z-pins, and after the heat is conducted out of the material surface, it cannot be diffused again, resulting in heat concentration. Summary of the Invention
[0007] The embodiments of the present application provide a three-dimensional highly thermally conductive pitch-based carbon fiber composite material and a preparation method thereof. Based on the method of reserving holes in prepregs, the Z-Pins are not easily broken, ensuring the integrity of the constructed Z thermal conduction path; the reserved holes ensure the regularity of the Z-direction thermal conduction path, and at the same time do not damage the continuity of the fiber filaments in the plane layer, ensuring the in-plane thermal conductivity.
[0008] The embodiments of the present application provide a preparation method of a three-dimensional highly thermally conductive pitch-based carbon fiber composite material, including: Select base fabrics with the required number of layers according to the required material thickness and performance, and prepare pitch-based carbon fiber prepregs, wherein the prepared pitch-based carbon fiber prepregs are reserved with a plurality of distributed reserved Pin holes; After the pitch-based carbon fiber raw filaments are pretreated, they are infiltrated in a resin solution, and subjected to twisting treatment, and after the twisting treatment, they are cut into a specified length and dried to prepare pitch-based carbon fiber short-cut Z-pins; Mix the pitch-based carbon fiber short-cut Z-pins with resin to make a pin-resin mixture; Fill the pin-resin mixture into the Pin holes of the pitch-based carbon fiber prepregs, and apply a magnetic field around the filled material to make a target proportion of the pitch-based carbon fiber short-cut Z-pins in the pin-resin mixture be in a state consistent with the Z direction; Cure the whole material after the magnetic field is applied; Apply high-thermal-conductivity material films on the upper and lower surfaces of the cured pitch-based carbon fiber composite material, and perform secondary curing to complete the preparation.
[0009] The embodiments of the present application further provide a three-dimensional highly thermally conductive pitch-based carbon fiber composite material, including: Pitch-based carbon fiber prepregs, reserved with Pin holes, which are prepared by selecting base fabrics with the required number of layers according to the required material thickness and performance; Pitch-based carbon fiber short-cut Z-pins, which are prepared by pretreating pitch-based carbon fiber raw filaments, infiltrating them in a resin solution, performing twisting treatment, and cutting them into a specified length and drying after the twisting treatment; The pitch-based carbon fiber short-cut Z-pins are implanted into the reserved Pin holes of the pitch-based carbon fiber prepregs; High-thermal-conductivity material films are covered on the upper and lower surfaces of the placed composite material.
[0010] The method of the present application is based on the method of pre-preg reserved holes. The Z-Pin is not easily broken, ensuring the integrity of the Z-direction heat conduction path of the structure. The reserved holes ensure the regularity of the Z-direction heat conduction path without destroying the continuity of the fiber filaments in the plane layer, ensuring the in-plane thermal conductivity. Based on the method of standing upright by a strong magnetic field, it ensures the efficient standing upright of the Z-Pin, improves the efficiency, and can ensure the standing proportion of the Z-Pin by controlling the magnetic field, ensuring the stability of the formed Z-direction heat conduction path.
[0011] The above description is only an overview of the technical solution of the present application. In order to be able to understand the technical means of the present application more clearly, it can be implemented according to the content of the specification. And in order to make the above and other purposes, features and advantages of the present application more obvious and understandable, the following specifically illustrates the specific implementation manners of the present application. Brief Description of the Drawings
[0012] By reading the following detailed description of the preferred embodiments, various other advantages and benefits will become clear to those of ordinary skill in the art. The drawings are only for the purpose of showing the preferred embodiments and are not considered to be a limitation of the present application. And throughout the drawings, the same reference numerals are used to represent the same components. In the drawings: Figure 1 It is a schematic diagram of the basic process for the preparation method of the three-dimensional high thermal conductivity asphalt-based carbon fiber composite material in the embodiment of the present application; Figure 2 It is a schematic diagram of the structure of the asphalt-based carbon fiber composite material prepared in the embodiment of the present application; Figure 3 It is a schematic diagram of the interweaving of warp and weft yarns in the preparation method of the embodiment of the present application; Figure 4 It is a schematic diagram of the unidirectional weaving method in the preparation method of the embodiment of the present application; Figure 5 It is a schematic diagram of the Pin holes of the unidirectional weaving method in the preparation method of the embodiment of the present application; Figure 6 It is a schematic diagram of standing up the Z-pin by applying a magnetic field in the preparation method of the embodiment of the present application; Figure 7 It is a schematic diagram of the cross-sectional structure of the asphalt-based carbon fiber composite material prepared in the embodiment of the present application; Figure 8 It is a partial schematic diagram of a single reserved hole of the asphalt-based carbon fiber composite material prepared in the embodiment of the present application. Detailed Description of the Specific Embodiments
[0013] Exemplary embodiments of the present disclosure will be described in more detail below with reference to the accompanying drawings. Although the exemplary embodiments of the present disclosure are shown in the drawings, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided so that the present disclosure can be more thoroughly understood and the scope of the present disclosure can be completely conveyed to those skilled in the art.
[0014] With the rapid development of industries such as 5G / 6G communication, satellite Internet, radar detection, etc., electronic products are rapidly developing towards high power, miniaturization, and high density. The power of electronic devices has been greatly improved, and the heat dissipation space has been continuously reduced. The heat dissipation problem has become a prominent problem restricting its development and is likely to affect the device performance. The industry is using various means to solve the heat dissipation problem, and composite materials have become one of the advantageous methods. Asphalt-based carbon fiber composites have become preferred thermal conductive materials due to their excellent properties such as high temperature resistance, high strength and high modulus, and low density. They can improve the mechanical properties and thermal conductivity of products and significantly reduce weight. Many enterprises in China have mastered the technology for mass production of asphalt-based carbon fibers, and domestic companies have prepared mesophase asphalt-based carbon fibers with a thermal conductivity of 900 W / m•K. Carbon nanotubes and graphene materials also have excellent thermal conductivity, but it is still very difficult to prepare them in large sizes and large quantities, and the thermal conductivity of these two materials is unstable when prepared into composite materials. Therefore, they are not widely used in products. Asphalt-based carbon fiber composites have a wide range of application requirements in the thermal management systems of application fields such as satellites, hypersonic aircraft, nuclear energy, military, and electronics due to their characteristics of lightweight, high thermal conductivity, high modulus, and stability.
[0015] However, currently, the asphalt-based carbon fiber composites that can be applied in engineering only have a very high thermal conductivity in the planar direction, with an average of 300 - 400 W / m•K, while the thermal conductivity in the Z direction is extremely low. The better ones only achieve about 0.8 W / m•K, and in some laboratories and patents, it can reach about 10 W / m•K. Because carbon fiber composites generally use a resin matrix as the bonding layer during preparation, and the thermal conductivity of the resin is extremely low, the heat transfer path in the Z direction is blocked. However, for the application of carbon fiber composites in products, the thermal conductivity requirement in the Z direction is very high. Larger heat-generating components are attached to the wall and rely on the thermal conductivity in the Z direction to conduct heat to the outer surface and then spread out. The low thermal conductivity in the Z direction restricts the application of this material.
[0016] Currently, some publicly available technologies are dedicated to improving the thermal conductivity of carbon fiber composites in the Z direction, but the common problems are: the thermal conductivity effect in the Z direction shown in the examples is average and unstable; the diffusion after heat conduction is not considered, and heat concentration is likely to occur, leading to device damage.
[0017] If a simple heat-conducting structure could be provided in the Z-direction of a carbon fiber composite material as a heat transfer path, it would not only solve the problem of impeded Z-direction heat transfer, but also provide good structural strength and relatively stable heat transfer. It would also enable low-cost, simple processing, and make mass production and engineering feasible. A similar invention to the present invention, and one that serves as a foundation for the present invention, is the three-dimensional heat transfer channel composite material and its preparation method disclosed in CN109049865A. This method involves constructing fiber Z-pins or metal needles as thermal reinforcements, which are then implanted in the Z-direction of the composite material to establish a heat transfer channel. This method can also improve interlaminar shear performance. However, the Z-pins mentioned in this method are sharpened for insertion into the composite material, which damages the carbon fiber layers and places high demands on operability. Furthermore, the Z-pins may break or break due to internal stamping resistance during insertion, resulting in a maximum Z-direction thermal conductivity of only 10 W / m·K. Furthermore, heat is concentrated at a single point on the composite material surface after being conducted through the sharpened Z-pins, preventing heat from dissipating on the outer surface of the material. Consequently, this method fails to provide both conduction and heat dissipation for electronic products.
[0018] The present application embodiment proposes a method for preparing a three-dimensional high thermal conductivity asphalt-based carbon fiber composite material, such as Figure 1 Shown, including: In step S101, a base cloth with a required number of layers is selected according to the required material thickness and performance, and an asphalt-based carbon fiber prepreg is prepared, wherein the prepared asphalt-based carbon fiber prepreg is reserved with a plurality of distributed reserved Pin holes. In a specific example, the asphalt-based carbon fiber base cloth can be first woven with fiber filaments, and then the base cloth with a required number of layers is selected according to the required material thickness and performance, the holes are aligned and stacked, and the base cloth is impregnated in resin, or the resin is brushed between the base cloth layers. The method of the embodiment of the present application reserves Pin holes when the asphalt-based carbon fiber prepreg is woven and layered, so that the Z-pin implantation does not destroy its own performance, nor does it destroy the fiber continuity of the base cloth, thereby ensuring the in-plane thermal conductivity and mechanical properties.
[0019] In step S102, the asphalt-based carbon fiber precursor, after pretreatment, is impregnated with a resin solution and twisted. After twisting, the asphalt-based carbon fiber chopped Z-pins are cut into a specified length and dried to produce the asphalt-based carbon fiber chopped Z-pins. In a specific example, the asphalt-based carbon fiber precursor can be pretreated by removing surface curing agent residues using methods such as ultrasonic vibration; then impregnated and twisted, the carbon fiber filaments are immersed in the resin solution for 30-60 seconds and twisted, preferably with a twist specification of 20-30 twists / m; then pre-dried; and the fiber bundles are cut into a specified length c.
[0020] In step S103, the chopped asphalt-based carbon fiber Z-pins are mixed with the resin to make a pin-resin mixture. In a specific example, a large amount of chopped asphalt-based carbon fiber Z-pins are mixed with the resin to make a pin-resin mixture. The density of the chopped asphalt-based carbon fiber Z-pins in the pin-resin mixture is about 1 cm 3 The mixture contains 200 - 1000 Z-pins per cm
[0021] Through the above steps, an uncured asphalt-based carbon fiber prepreg with reserved array Pin holes and a pin-resin mixture of chopped asphalt-based carbon fiber Z-pins and resin have been formed. In step S104, the pin-resin mixture is filled into the Pin holes of the asphalt-based carbon fiber prepreg, and a magnetic field is applied around the filled material to make a target proportion of the chopped asphalt-based carbon fiber Z-pins in the pin-resin mixture be in a state consistent with the Z direction. In a specific example, the pin-resin mixture is filled into the reserved holes on the asphalt-based carbon fiber prepreg manually or automatically, and then devices such as electromagnets, permanent magnets or electromagnetic coils are used to create the required magnetic field around it. Utilizing the diamagnetism of the chopped asphalt-based carbon fiber Z-pins in the pin-resin mixture, they are subjected to a torque perpendicular to the magnetic force direction in the magnetic field and stand upright in a state consistent with the Z direction. This application uses a magnetic field to make a large number of Z-pins stand upright and constructs a complete and stable Z-direction heat conduction path.
[0022] In step S105, the whole material after the magnetic field is applied is cured; In step S106, high thermal conductivity material films are laminated on the upper and lower surfaces of the cured asphalt-based carbon fiber composite material and cured for the second time to complete the preparation. The method of this application coats high thermal conductivity materials on the upper and lower surfaces of the asphalt-based carbon fiber composite material after curing and forming, and then cures and forms again. The heat conducted to a point on the material surface is evenly diffused on the whole surface, forming secondary heat dissipation and comprehensive conduction. The whole technological process is highly efficient, low-cost and convenient for engineering application.
[0023] As Figure 2 shown, the prepared carbon fiber composite material includes an asphalt-based carbon fiber prepreg 1, a pin-resin mixture 2, a high thermal conductivity material film 3, an asphalt-based carbon fiber base cloth 11, and a resin 12.
[0024] For the method based on the reserved holes of the prepreg in this application, the Z-Pins are not easily broken, ensuring the integrity of the constructed Z-direction heat conduction path; the reserved holes ensure the regularity of the Z-direction heat conduction path, and at the same time do not damage the continuity of the fiber filaments in the plane layer, ensuring the in-plane thermal conductivity.
[0025] For the woven base cloth, this application provides two methods. In some embodiments, preparing the asphalt-based carbon fiber prepreg includes: It is formed by the interweaving of warp yarns and weft yarns, and Pin holes are reserved during weaving. As Figure 3 shown, a cluster of pitch-based carbon fiber tows is used as the warp yarn, and plain weave or twill weave methods are adopted. This method is simple to operate and is convenient for forming uniform and a certain number of interweaving holes. The arrangement of the interweaving holes is very regular, and it is easier to form a rectangular array, which is convenient for the uniformity of heat transfer.
[0026] In the case of plain weave, a cluster of warp yarns or weft yarns includes 3K - 6K fiber filaments / bundles. The distance between warp yarns and the distance between weft yarns are both a, so as to ensure that the woven base fabric reserves Pin holes in an array. The Pin holes are rectangular holes with a side length of a and a distance of b, satisfying: 0.8h < a < 1.1h, 2a < b < 4a, where h is the thickness of the pitch-based carbon fiber prepreg.
[0027] The thickness of the woven base fabric can be 0.125mm - 0.5mm. This method reserves Pin holes without damaging the continuity of the fiber filaments, and is more controllable during operation, very conveniently obtaining the required number and spacing of Pin holes, which is convenient for forming arrays of rectangular, circular or other regular shapes.
[0028] Another way of weaving the base fabric. In some embodiments, preparing the pitch-based carbon fiber prepreg includes: Adopting the unidirectional weaving method, laying the pitch-based carbon fiber filaments flat in one direction. As Figure 4 shown, needles with the required diameter are inserted in advance at corresponding positions to reserve Pin holes.
[0029] Alternatively, a combined weaving method with different angles can also be adopted. The pitch-based carbon fiber filaments are combined along woven layers at different angles to form multiple layers of carbon fiber filament layers. The fiber filaments of the single-directional weaving are spread out, and needles with the required diameter are inserted in advance at corresponding positions to reserve Pin holes. As Figure 4 shown in the figure for inserting needles to reserve pin holes. For example, the pitch-based carbon fiber filaments are combined along woven layers at 0 degrees, 45 degrees, and 90 degrees to form multiple layers of carbon fiber filament layers, and needles with the required diameter are also inserted in advance at corresponding positions to reserve Pin holes.
[0030] The inserted pin holes are circular holes. As Figure 5 shown, the diameter is r, and the distance between Pin holes is b, satisfying: 0.9h < r < 1.2h, 2r < b < 4r, where h is the thickness of the pitch-based carbon fiber prepreg.
[0031] The thickness of the woven base fabric is 0.125mm - 0.5mm. This method reserves Pin holes without damaging the continuity of the fiber filaments, and is more controllable during operation, very conveniently obtaining the required number and spacing of Pin holes, which is convenient for forming arrays of rectangular, circular, or other regular shapes.
[0032] After obtaining the base fabric with reserved Pin holes by using the above two methods, immerse it in resin or apply resin between the base fabric layers to form an uncured asphalt-based carbon fiber prepreg with reserved Pin holes. The immersion method is recommended, which is more suitable for the brittle characteristics of the asphalt-based carbon fiber material.
[0033] Regarding the values of a, r, and b proposed in this application: The designed values of a, r, and b in this application are within the ranges of a and r values proposed in this application. At the completion of the subsequent steps, the Z-pin density and the integrity of the erected ones inside are optimal, ensuring the heat transfer path in the Z direction. Within the range of the b value proposed in this application, it can ensure that the number of heat transfer paths in the Z direction is sufficient at the completion of the subsequent steps, while ensuring the most complete heat transfer path of the in-plane fibers.
[0034] In the implementation example of this application, an asphalt-based carbon fiber prepreg with a thickness of 1.8 mm is prepared. The base fabric woven by Method 1 and Method 2 has a = 2 mm, b = 6.5 mm, the thickness of each layer of the base fabric is 0.2 mm, and the resin layer thickness is 0.6 - 0.7 mm. Thus, an asphalt-based carbon fiber composite plate with high thermal conductivity and a thickness of 2 mm can be obtained. In the subsequent steps, the thickness of the film covering the upper and lower surfaces is approximately 0.1 mm.
[0035] In some embodiments, the preparation of short-cut asphalt-based carbon fiber Z-pins includes: After the asphalt-based carbon fiber raw filaments are pretreated, immerse them in the resin solution for 30 - 60 s, twist them, pre-dry them. The twisting specification is 20 - 30 twists / m, and then pre-dry them again. The method of pre-drying: the temperature is 120 - 180 °C, and in this application, they are dried at 130 °C for 10 min. The method of drying and curing: the temperature is 180 - 250 °C, and in this application, they are dried at 180 °C for 50 min. The resin impregnated by the carbon fiber filaments is preferably epoxy resin, and the pin-resin mixture can be epoxy resin, which has good thermal conductivity and a small curing shrinkage rate. In a specific example, the epoxy resin can be glycidyl ether type epoxy resin, or bisphenol A type epoxy resin, glycidyl ester type epoxy resin, glycidyl amine type epoxy resin.
[0036] Cut the pre-dried fiber bundle into a specified length c and cure it to obtain short-cut asphalt-based carbon fiber Z-pins, where c > h + 0.6 mm. (h is the thickness of the asphalt-based carbon fiber prepreg), and the diameter of the Z-pins after drying and curing is 8 - 17 μm.
[0037] The diameter of the short-cut asphalt-based carbon fiber Z-pins prepared in this application is about 8 - 10 μm after being processed by the above steps; for an asphalt-based carbon fiber prepreg with a thickness of 1.8 mm, the length of the short-cut asphalt-based carbon fiber Z-pins prepared in this application is 2.4 mm.
[0038] The advantages of the Z-pin formed by the method of the present application are as follows: the surface curing molding reduces resin loss; the infiltration method helps to make the resin evenly distributed; the semi-cured state is formed under pre-drying to ensure mild cross-linking of the resin and certain viscosity, which is convenient for cutting; finally, drying and curing are carried out to ensure good fracture resistance.
[0039] After that, a large number of short-cut asphalt-based carbon fiber Z-pins are mixed with resin to make a pin-resin mixture. The density of the short-cut asphalt-based carbon fiber Z-pins in the pin-resin mixture is about 1 cm 3 The mixture contains 200 - 1000 Z-pins.
[0040] Through the above steps, an uncured asphalt-based carbon fiber prepreg with reserved array Pin holes and a pin-resin mixture of short-cut asphalt-based carbon fiber Z-pins and resin have been formed. On this basis, in some embodiments, applying a magnetic field around the filled material includes: Using a magnetic device to generate a required magnetic field around the prepreg filled with the resin mixture of short-cut asphalt-based carbon fiber Z-pins, so as to use the generated magnetic field to make the Z-pins rotate around an axis perpendicular to the magnetic field, making the long axis of the short-cut asphalt-based carbon fiber Z-pins parallel to the magnetic field direction.
[0041] In a specific example, as Figure 6 shown, the pin-resin mixture can be filled into the reserved holes on the asphalt-based carbon fiber prepreg manually or automatically, and then a required magnetic field is created around it using devices such as electromagnets, permanent magnets or electromagnetic coils. Utilizing the diamagnetism of the short-cut asphalt-based carbon fiber Z-pins in the pin-resin mixture, they are subjected to a torque perpendicular to the magnetic force direction in the magnetic field and stand upright in a state consistent with the Z direction.
[0042] Since the length c of the Z-pin > h + 0.6 mm (h is the thickness of the asphalt-based carbon fiber prepreg), the Z-pin can pass through the holes in the prepreg. As Figure 6 shown, about 0.3 mm of allowance of the Z-pin is exposed above and below the upper and lower surfaces of the prepreg respectively, and thus the implantation of the Z-pin in the reserved holes is completed.
[0043] The benefits of the reserved holes in the asphalt-based carbon fiber prepreg of the embodiment of the present application are reflected in this process.
[0044] Firstly, the resistance is very small when implanting and standing the Z-pin upright, the perforation is easy, the implantation speed is fast, the force on the Z-pin can be reduced, and the uncured resin has a buffering effect on the Z-pin, making it not easy to break when inserted.
[0045] Second, during the erection process of the Z-pin, the fiber continuity of the original carbon fiber base fabric is not affected, ensuring its in-plane heat conduction path and mechanical properties. The existing implantation method is to directly insert the Z-pin into the uncured carbon fiber material, and the punching area will damage the integrity of the carbon fiber plane layer; moreover, the inserted Z-pin is subject to the resistance of the carbon fiber plane layer, with relatively large deflection angles and is prone to breakage, damaging the Z-direction heat conduction path. The method provided by the present invention has an average deflection angle of the inserted Z-pin measured to be 3-5°, which is several to dozens of times smaller than the existing method of implanting Z-pin.
[0046] The method of filling the pin-resin mixture into the reserved holes in this application can adopt manual filling and automated filling methods. The specific implementation methods are as follows: The manual implantation method, that is, using a dispensing tool to insert the pin-resin mixture into the pitch-based carbon fiber prepreg one by one. The pitch-based carbon fiber prepreg is fixed in advance with a fixture, and pay attention to keeping each reserved hole filled when manually inserting. This method is simple to operate and has low cost, but it is time-consuming due to the large number of reserved holes, and this method can be adopted in non-batch or large-area material production.
[0047] The automated filling method is to first fix the pitch-based carbon fiber prepreg with a fixture in advance, and then use a dispensing machine or a tooling equipped with the required equipment to pick up the Z-pins in rows or arrays, align them with the reserved hole positions on the pitch-based carbon fiber prepreg to be formed, and realize row filling or surface filling. This method has high efficiency, ensures that the angles and distances of multiple Z-pins implanted are the same, and ensures uniform heat conduction. Using the automatic implantation method of a dispensing machine, the implantation rate can reach one hole / 0.3s.
[0048] The specific method of using a magnetic field to erect the Z-pin is described as follows. Since each reserved hole is filled with a pin-resin mixture containing thousands of short-cut pitch-based carbon fiber Z-pins, these Z-pins are in a random position state, and their diameters are small and not convenient for picking up and erection. Therefore, at this time, the Z-direction heat transfer channel has not been established yet. The embodiment of this application proposes a method of applying a magnetic field to erect the Z-pin, including: First, use equipment such as electromagnets, permanent magnets, or electromagnetic coils to create the required magnetic field around the prepreg filled with the pin-resin mixture. Since pitch-based carbon fiber has diamagnetic characteristics (its magnetic susceptibility is extremely low and negative), it is subjected to a torque perpendicular to the magnetic field direction in the magnetic field, generating a phenomenon of micro-magnetization opposite to the external magnetic field direction (i.e., the magnetic induction line direction), and its axial diamagnetism is weaker than its radial diamagnetism. Therefore, the radial direction is more easily repelled by the magnetic field, resulting in the Z-pin rotating around the axis perpendicular to the magnetic field, and finally the long axis of the Z-pin is parallel to the magnetic field direction (magnetic induction line direction).
[0049] When a magnetic field is applied, the stronger the magnetic field intensity, the higher the degree of orientation of the Z-pins, but the higher the energy consumption. In some embodiments, at a pin-resin mixture density of 300 - 500 Z-pins / cm 3 Under the condition of a pin-resin mixture density of the mixture, with a Z-pin diameter of 8 - 17 μm and a length of 1.5 - 3.5 mm, a magnetic field intensity of 0.15 T - 1.5 T, and more preferably, 0.3 T - 0.5 T. When the magnetic field is constructed using permanent magnets, trapezoidal permanent magnets can be used, and the distance between the upper and lower permanent magnets and the prepreg should be maintained at 2 - 10 mm. An overly large distance requires an increase in the magnetic field intensity, while an overly small distance easily causes the permanent magnets to be contaminated with the resin solution and unable to be reused. Under the condition that the Z-pins are 2.4 mm long and 8 - 10 μm in diameter, experimental results have shown that the number of Z-pins has no obvious effect on the magnetic field intensity, but the length and diameter of the Z-pins have an effect on the proportion of them standing upright. The longer the length and the larger the diameter, the greater the magnetic field required when the standing ratio is the same. In this embodiment, under the condition of 0.35 T and a suitable concentration of epoxy resin, using a microscope to observe and calculate can ensure that the standing ratio of the above Z-pins > 30%. If modified pitch-based carbon fibers are used, that is, a magnetic layer such as nickel is coated on the outer surface of the fibers, the standing ratio > 70%.
[0050] After applying a magnetic field to make a suitable ratio of Z-pins stand upright, the magnetic field needs to be kept uniform and stable to ensure that the forces acting on the standing Z-pins are the same and achieve a regular aligned state. Then, the magnetic field intensity and direction can be finely adjusted, or a local magnetic field can be applied or adjusted, while observing in real time using an optical microscope to make the Z-pins slightly protrude above the upper and lower surfaces of the pitch-based carbon fiber prepreg. Since the length c of the Z-pins > h + 0.6 mm (h is the thickness of the pitch-based carbon fiber prepreg), this can be achieved. The implementation experience of this application is to first apply a weak magnetic field to initially stand the Z-pins upright, and then gradually increase the uniform magnetic field to a strength of 0.35 T. It can be weakened and then increased to make the heights of the Z-pins basically the same when standing upright, and they are basically aligned up and down and protrude from the prepreg surface.
[0051] In some embodiments, curing the entire material after applying the magnetic field includes: Implanting short-cut Z-pins of pitch-based carbon fibers into the reserved holes of the pitch-based carbon fiber prepreg, and placing the whole into a mold for pressure curing. First, heat up in an autoclave or a hot press molding machine at a heating rate of 2 - 5 °C / min. After heating to 100 - 180 °C, start applying pressure. Depending on the different environmental requirements of the material, the pressure is controlled at 0.4 - 1.2 Mpa. For the general epoxy resin material used in the embodiment, in the specific implementation, start applying pressure after heating to 130 - 140 °C, steadily heat up at 3 °C / min, and apply a pressure of 1 Mpa to ensure the material quality and relatively save energy consumption.
[0052] After curing, the carbon fiber is short and the Z-pins will slightly protrude from the upper and lower surfaces of the formed pitch-based carbon fiber composite material. Shearing is required to ensure a flat surface. Fix the position of the pitch-based carbon fiber composite material with a fixture, position it through a guide block with wire perforations, and use a small grinding wheel or polishing machine to perform fine shearing on its surface. When necessary, equipment such as a laser can be used to check the flatness of the surface. According to the above implementation scheme, the present invention can achieve a surface flatness ≤ 0.05 mm after Z-pin excision.
[0053] On the basis of the foregoing steps, a stable heat conduction path in the Z direction of the pitch-based carbon fiber composite material prepared in this application has been established. The path is complete without fractures and the quantity is sufficient, and heat can be conducted from one side of the material to the other side. However, for actual high heat consumption electronic products, their high heat points are usually relatively concentrated, for example, concentrated on a certain component or chip. Therefore, after the heat is exported, it still needs to be diffused on the outer surface of the housing. In some embodiments, a high thermal conductivity material film is further coated on the upper and lower surfaces of the pitch-based carbon fiber composite material, such as Figure 7 , Figure 8 As shown, high thermal conductivity material films 3 are coated on the upper and lower surfaces of the composite material. Figure 8 Among them, most of the erected Z-pins are included between the prepregs and then cured and formed. The method proposed in this application for preparing a high thermal conductivity material film on the upper and lower surfaces of the pitch-based carbon fiber composite material can evenly diffuse the heat conducted to a point on the material surface over the entire surface, forming secondary heat dissipation and comprehensive conduction.
[0054] Prepare a high thermal conductivity material film on the upper and lower surfaces of the composite material. The materials can be selected from metal copper, metal aluminum, carbon nanotubes, graphene, etc. In the specific implementation of the embodiment, copper can be coated on the Z-pins to increase the thermal conductivity under the condition of low cost. Thermal spraying and electroplating can be used. When the area is small and the appearance quality requirements are not high, thermal spraying is selected to reduce costs and facilitate operation. When the area is large and the appearance quality requirements are high, electroplating is selected. In a specific example, after surface copper plating, natural drying and curing, heat curing, ultraviolet curing, adding curing agents, etc. can be used, or ultraviolet curing can also be used, which has a lower cost and better curing effect.
[0055] According to the embodiment of this application, the composite material prepared therefrom is tested to have an in-plane thermal conductivity > 400 W / m•K and a Z-direction thermal conductivity > 50 W / m•K.
[0056] The method of this application first weaves an asphalt-based carbon fiber base fabric with reserved array Pin holes. Two-dimensional weaving or one-way laying and pinning methods can be used to ensure that the fiber continuity of the base fabric is not damaged while reserving the holes. Then, the base fabric is infiltrated with resin to form a prepreg containing reserved holes. Then, asphalt-based carbon fiber Z-pins are made from asphalt-based carbon fiber raw filaments, and they are mixed with resin to form a pin-resin mixture. Next, the pin-resin mixture is filled into each reserved hole by manual or automated implantation. By applying a magnetic field, the short-cut Z-pins in the mixture are made to stand upright parallel to the Z-direction of the material, and the magnetic field is adjusted to make the heights of the Z-pins consistent. Thus, a certain number of Z-direction conduction paths are ensured in the array holes. Then, the prepreg is cured under high temperature and pressure, and the protruding Z-pins on the upper and lower surfaces are trimmed to be flush with the upper and lower surfaces of the material. Finally, thin films of high thermal conductivity materials are prepared on the upper and lower surfaces of the composite material, and it is cured again to form heat diffusion paths on the surface.
[0057] Based on the method of standing upright by a strong magnetic field, this application ensures the efficient standing upright of Z-Pins, improves efficiency, and can ensure the standing-up proportion of Z-Pins by controlling the magnetic field, ensuring the stability of the formed Z-direction heat conduction paths.
[0058] After the heat reaches the outer surface of the material through the Z-direction, it can be evenly diffused a second time, enabling the heat of the device to quickly disperse after conducting out of the product, truly achieving the effect of heat dissipation.
[0059] The embodiment of this application also proposes a three-dimensional high thermal conductivity asphalt-based carbon fiber composite material, including: An asphalt-based carbon fiber prepreg with reserved Pin holes, which is prepared by selecting the base fabric of the required number of layers according to the required material thickness and performance; Asphalt-based carbon fiber short-cut Z-pins, which are prepared by pretreating asphalt-based carbon fiber raw filaments, infiltrating them in a resin solution, twisting them, and cutting them to a specified length and drying them after the twisting treatment; The asphalt-based carbon fiber short-cut Z-pins are implanted into the reserved Pin holes of the asphalt-based carbon fiber prepreg; High thermal conductivity material films are covered on the upper and lower surfaces of the placed composite material.
[0060] In some embodiments, implanting the asphalt-based carbon fiber short-cut Z-pins into the reserved Pin holes of the asphalt-based carbon fiber prepreg is achieved in the following manner: Mix the asphalt-based carbon fiber short-cut Z-pins with resin to make a pin-resin mixture; Fill the pin-resin mixture into the Pin holes of the asphalt-based carbon fiber prepreg, and apply a magnetic field around the filled material to make a target proportion of the asphalt-based carbon fiber short-cut Z-pins in the pin-resin mixture be in a state consistent with the Z-direction; Cure the whole material after applying a magnetic field.
[0061] In some embodiments, at a density of the pin-resin mixture of the mixture of 300 - 500 Z-pins / 1 cm, a Z-pin diameter of 8 - 17 μm, and a length of 1.5 - 3.5 mm, the magnetic field strength is 0.15 T - 1.5 T. 3 Under the conditions of the pin-resin mixture density of the mixture, the Z-pin diameter of 8 - 17 μm, and the length of 1.5 - 3.5 mm, the magnetic field strength is 0.15 T - 1.5 T.
[0062] It should be noted that in the embodiments of the present application, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements not only includes those elements, but also includes other elements not expressly listed, or further includes elements inherent to such process, method, article or device. Without further limitation, an element defined by the statement "including a..." does not exclude the existence of additional identical elements in the process, method, article or device including the element.
[0063] The serial numbers of the embodiments of the present application above are only for description and do not represent the advantages or disadvantages of the embodiments.
[0064] The embodiments of the present application have been described above in conjunction with the accompanying drawings. However, the present application is not limited to the above specific embodiments. The above specific embodiments are merely illustrative and not restrictive. Under the inspiration of the present application, those of ordinary skill in the art can also make many forms without departing from the purpose of the present application and the scope protected by the claims. All of these are within the protection scope of the present application.
Claims
1. A preparation method of a three-dimensional highly thermally conductive asphalt-based carbon fiber composite material, characterized in that, Including: Select the base fabric with the required number of layers according to the required material thickness and performance, and prepare the pitch-based carbon fiber prepreg. Multiple reserved Pin holes are distributed in the prepared pitch-based carbon fiber prepreg; After the pitch-based carbon fiber raw yarn is pretreated, it is infiltrated in the resin solution, and then subjected to twisting treatment. After the twisting treatment, it is cut into a specified length and dried to prepare the pitch-based carbon fiber short cut Z-pin; Mix the pitch-based carbon fiber short cut Z-pin with the resin to make a pin-resin mixture; Fill the Pin holes of the pitch-based carbon fiber prepreg with the pin-resin mixture, and apply a magnetic field around the filled material to make a target proportion of the pitch-based carbon fiber short cut Z-pin in the pin-resin mixture be in a state consistent with the Z direction; Cure the whole material after the magnetic field is applied; Cover the upper and lower surfaces of the cured pitch-based carbon fiber composite material with a high thermal conductivity material and cure it for the second time to complete the preparation.
2. The preparation method of the three-dimensional highly thermally conductive asphalt-based carbon fiber composite material according to claim 1, characterized in that, Preparing the pitch-based carbon fiber prepreg includes: It is woven and formed by the interweaving of warp yarns and weft yarns. Pin holes are reserved during weaving, and plain weave or twill weave methods are used; In the case of using plain weave, a cluster of warp yarns or weft yarns includes 3K-6K fiber filaments / bundles. The distance between warp yarns and the distance between weft yarns are both a, so as to ensure that the reserved Pin holes of the woven base fabric form an array. The Pin holes are rectangular holes with a side length of a and a spacing of b, satisfying: 0.8h < a < 1.1h, 2a < b < 4a, where h is the thickness of the pitch-based carbon fiber prepreg.
3. The preparation method of the three-dimensional highly thermally conductive asphalt-based carbon fiber composite material according to claim 1, characterized in that, Preparing the pitch-based carbon fiber prepreg includes: Using the unidirectional weaving method, lay the pitch-based carbon fiber filaments flat in one direction, and insert needles with the required diameter in advance at the corresponding positions to reserve Pin holes; or, Using the combined weaving method with different angles, combine the pitch-based carbon fiber filaments along the woven layers at different angles to form multiple carbon fiber filament layers, and reserve Pin holes at the corresponding positions; The reserved pin holes are circular holes with a diameter of r, and the Pin hole spacing is b, satisfying: 0.9h < r < 1.2h, 2r < b < 4r, where h is the thickness of the pitch-based carbon fiber prepreg.
4. The preparation method of the three-dimensional highly thermally conductive asphalt-based carbon fiber composite material according to claim 2 or 3, characterized in that, Preparing the pitch-based carbon fiber short cut Z-pin includes: After the pitch-based carbon fiber raw yarn is pretreated, it is impregnated in the resin solution for 30s - 60s, twisted, and pre-dried. The twisting specification is 20 - 30 twists / m; Cut the pre-dried fiber bundle into a specified length c and cure it to obtain the pitch-based carbon fiber short cut Z-pin, where c > h + 0.6mm.
5. The preparation method of the three-dimensional high thermal conductivity asphalt-based carbon fiber composite material according to claim 2 or 3, characterized in that, Applying a magnetic field around the filled material includes: Using a magnetic device to generate the required magnetic field around the prepreg filled with the resin mixture of the pitch-based carbon fiber short cut Z-pin, so as to use the generated magnetic field to make the Z-pin rotate around the axis perpendicular to the magnetic field, so that the long axis of the pitch-based carbon fiber short cut Z-pin is parallel to the magnetic field direction.
6. The preparation method of the three-dimensional highly thermally conductive asphalt-based carbon fiber composite material according to claim 5, characterized in that, At 300 - 500 Z-pins / 1 cm 3 Under the conditions that the density of the pin-resin mixture of the mixture, the Z-pin diameter is 8 - 17 μm, and the length is 1.5 - 3.5 mm, the magnetic field strength is 0.15 T - 1.5 T.
7. The preparation method of the three-dimensional high thermal conductivity asphalt-based carbon fiber composite material according to claim 6, wherein, Curing the whole material after the magnetic field is applied includes: The short-cut Z-pins made of pitch-based carbon fiber are implanted into the reserved holes of the pitch-based carbon fiber prepreg, and the whole is placed into a mold for pressure curing. First, it is heated in an autoclave or a hot press molding machine at a heating rate of 2 - 5 °C / min. After heating to 100 - 180 °C, pressure is applied. According to the different environmental requirements of the material, the pressure is controlled at 0.4 - 1.2 Mpa; After curing, the excess Z-pins exposed on the upper and lower surfaces are trimmed.
8. A three-dimensional highly thermally conductive asphalt-based carbon fiber composite material, characterized in that, It includes: Pitch Based carbon fiber prepreg, with reserved Pin holes, which is prepared by selecting the required number of layers of base fabric according to the required material thickness and performance; Short-cut Z-pins made of pitch-based carbon fiber, which are prepared by pre-treating the pitch-based carbon fiber rovings, infiltrating them in a resin solution, and performing twisting treatment, and then cutting them into a specified length and drying after the twisting treatment; The short-cut Z-pins made of pitch-based carbon fiber are implanted into the reserved Pin holes of the pitch-based carbon fiber prepreg; High thermal conductivity material films are covered on the upper and lower surfaces of the placed composite material.
9. The three-dimensional highly thermally conductive asphalt-based carbon fiber composite material according to claim 8, characterized in that The implantation of the short-cut Z-pins made of pitch-based carbon fiber into the reserved Pin holes of the pitch-based carbon fiber prepreg is achieved in the following way: The short-cut Z-pins made of pitch-based carbon fiber are mixed with resin to make a pin-resin mixture; The pin-resin mixture is filled into the Pin holes of the pitch-based carbon fiber prepreg, and a magnetic field is applied around the filled material to make a target proportion of the short-cut Z-pins made of pitch-based carbon fiber in the pin-resin mixture be in a state consistent with the Z direction; The whole material after the magnetic field is applied is cured.
10. The three-dimensional highly thermally conductive asphalt-based carbon fiber composite material according to claim 9, characterized in that, At 300 - 500 Z-pins / 1 cm 3 Under the conditions that the density of the pin-resin mixture of the mixture, the Z-pin diameter is 8 - 17 μm, and the length is 1.5 - 3.5 mm, the magnetic field strength is 0.15 T - 1.5 T.
Citation Information
Patent Citations
Three-dimensional thermal transfer channel composite material and preparation method thereof
CN109049865A
3D heat-conduction composite material and preparation method thereof
CN109265919A
Modified asphalt-based carbon fiber composite material for spacecraft load structure
CN111319279A
High-thermal-conductivity composite material and preparation method thereof
CN111962294A
Ceramic and preparation method and application thereof
CN117326882A